Mother’s Knowledge and Attitude about Breast Feeding Influence Her Empowerment to Decision for a Successfully Breast Feeding - Homa Mosaffa Khomami (Journal of Global Pharma Technology, 2017)
Background: The World Health Organization (WHO) and the American Academy of Pediatrics (AAP) recommend breastfeeding as the appropriate method of infant feeding. Empowering women to breastfeed gives women the ability to act and the right to do so. Empowerment of women, similar to freedom of choice breastfeeding, could be the one of goals of a positive quality of life. The present paper has been carried out to investigate knowledge and attitude of mothers refer to Lahijan Urban Health center during one year after delivery about breast feeding benefits. Materials and methods: This research was a descriptive cross-sectional study which had been done with quantitative and qualitative method in between 2013-2014. Data collection method was direct interview and questionnaire. 120 mothers were selected by Stratified Random sampling method. For data collection and data analysis use descriptive and analytical statistics. Then frequency tables achievement and for data analysis use correlation, analysis variance, X2 and T-test. Results: According to present study, most of the samples were in the range of 21-30 years old (57.5%) and most of them received information about breastfeeding(87.5%), resource of information was a collection of different resource(62.7%), Actually , half of samples had low knowledge(50.8%) and middle attitude (57.5%)about breastfeeding benefits. Pearson correlation showed a direct and positive relationship between knowledge and attitude of case studied (p< 0.0001, R= 0.35).Analysis variant Test showed a significant difference between mothers graduate and their knowledge (p< 0.0001). Discussion: study results showed the most of mothers had low and middle knowledge about breastfeeding benefit and then they need to education. Keywords: Breast Feeding, Empowerment, Knowledge, Attitude.